KAJIAN USULAN PERUBAHAN SISTEM PENYUSUNAN PERENCANAAN PROGRAM DAN PENGANGGARAN BERBASISKAN KOMPETISI BAGI POLITEKNIK MANUFAKTUR NEGERI BANDUNG - Dindin Sulaeman (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2011)
Politeknik Manufaktur Negeri Bandung (Polman) based on the Polman grand planning strategy, this period enter collaboration phase between Polman with the institution, which comes from inside of Indonesia and abroad. Based on theimplementation of the regulations as well as UU no 20/1997 about Penerimaan Negara Bukan Pajak (PNBP), PP no 22/1997 about Cara dan Penyetoran PNBP and UU no 20/2003 about the National Education System brought the impact on to institution. For that reasons Polmanshould be change the status from the Perguruan Tinggi Negeri (PTN) became Badan layanan Umum (BLU).The objective of this research was anticipated of transition period from PTN â€“ PTBLU by means of changing and making the planning mechanism, monitoring & evaluation as well as accountability reports so that in this transition periodPolmancould operate more effective and efficient as well as could develop independently from stakeholder especially from the government. Through the approach of 7S model of McKinsey the research that was not carried out for all the components, but it was limited to one â€œhard Sâ€, that is S for SystemHopefully in the future, Polmancould prepare their operational more effectively and efficiently due to the PDCA cycle and able to develop continuously and survives independently with out support of stakeholders, especial from government.